Inhibition of Major Histocompatibility Complex Class I Antigen Presentation in Pig and Primate Cells by Herpes Simplex Virus Type 1 and 2 ICP47 - Jugovic, Pieter (American Society for Microbiology, 1998)
Herpes simplex virus types 1 and 2 (HSV-1 and HSV-2) express an immediate-early protein, ICP47, that effectively inhibits the human transporter associated with antigen presentation (TAP), blocking major histocompatibility complex (MHC) class I antigen presentation to CD8(+) T cells. Previous work indicated that the mouse TAP is relatively resistant to inhibition by the HSV-1 and HSV-2 ICP47 proteins (ICP47-1 and ICP47-2) and that mouse cells infected with HSV-1 are lysed by anti-HSV CD8(+) cytotoxic T lymphocytes (CTL). Therefore, mice are apparently not suitable animals in which to study the in vivo effects of ICP47. In order to find an animal model, we introduced ICP47-1 and ICP47-2 into cells from various animal species—mice, rats, guinea pigs, rabbits, dogs, pigs, cows, monkeys, and humans—and measured TAP activity in the cells. Both proteins were unable to inhibit TAP in mouse, rat, guinea pig, and rabbit cells. In contrast, ICP47-1 and ICP47-2 inhibited TAP in pig, dog, cow, and monkey cells, and the TAP in pig and dog fibroblasts was often more sensitive to both proteins than TAP in human fibroblasts. These results were extended by measuring CD8(+)-T-cell recognition (CTL lysis) of cells from various species. Cells were infected with recombinant HSV-1 constructed to express murine MHC class I proteins so that the cells would be recognized and lysed by well-characterized murine anti-HSV CTL unless antigen presentation was blocked by ICP47. Anti-HSV CD8(+) CTL effectively lysed pig and primate cells infected with a recombinant HSV-1 ICP47(−) mutant but were unable to lyse pig or primate cells infected with a recombinant HSV-1 that expressed ICP47. Therefore, pigs, dogs, and monkeys may be useful animal models in which to test the effects of ICP47 on HSV pathogenesis or the use of ICP47 as a selective immunosuppressive agent.